2016
DOI: 10.1007/s40271-016-0190-z
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D Health Utility Scores: Data from a Comprehensive Canadian Cancer Centre

Abstract: This work represents the first set of HU scores for numerous cancer sites derived using Canadian preference weights. The dataset demonstrated construct validity and HU scores varied by general socio-demographic and clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 40 publications
2
43
1
1
Order By: Relevance
“…Results of the present study revealed that patients with poor mobility, great pain/discomfort and high anxiety/depression had lower HRQoL, which is consistent with previous research results (Kim & Kim, ; Naik et al., ). These results indicate that physical and psychological conditions are important factors that influence quality of life.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Results of the present study revealed that patients with poor mobility, great pain/discomfort and high anxiety/depression had lower HRQoL, which is consistent with previous research results (Kim & Kim, ; Naik et al., ). These results indicate that physical and psychological conditions are important factors that influence quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…The cancer survivors in the present study had an EQ‐5D index score of 0.55, which was lower than the scores obtained by Naik et al. () and Grutters et al. ().…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Полученные данные еще раз подтвер-дили мировой позитивный опыт применения данного оп-росника с целью оценки КЖ при широком спектре заболе-ваний и различных состояний [5,[15][16][17]. Компоненты опросника EQ-5D позволяли оценить КЖ пациентов с Пн, имели достаточно высокие корреляционные связи с ос-новными клинико-лабораторными показателями, т. е. обеспечивали возможность объективной оценки состоя-ния здоровья при Пн.…”
Section: Discussionunclassified